1998
DOI: 10.1126/science.279.5359.2083
|View full text |Cite
|
Sign up to set email alerts
|

Superfluidity Within a Small Helium-4 Cluster: The Microscopic Andronikashvili Experiment

Abstract: The infrared spectrum of single oxygen carbon sulfide (OCS) molecules was measured inside large superfluid pure helium-4 droplets and nonsuperfluid pure helium-3 droplets, both consisting of about 10(4) atoms. In the helium-4 droplets, sharp rotational lines were observed, whereas in helium-3 only a broad peak was found. This difference is interpreted as evidence that the narrow rotational lines, which imply free rotations, are a microscopic manifestation of superfluidity. Upon addition of 60 helium-4 atoms to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

22
610
3
7

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 620 publications
(643 citation statements)
references
References 22 publications
22
610
3
7
Order By: Relevance
“…7 (a)), the relative amplitudes only decrease in the case of the high-lying level beats (4,5) and (5,6), whereas the lower beats (3, 4) remain constant or even rise [(0, 1), (1,2), and (2, 3)] in amplitude in proportion to the sum of all.…”
Section: B Numerical Simulationmentioning
confidence: 99%
“…7 (a)), the relative amplitudes only decrease in the case of the high-lying level beats (4,5) and (5,6), whereas the lower beats (3, 4) remain constant or even rise [(0, 1), (1,2), and (2, 3)] in amplitude in proportion to the sum of all.…”
Section: B Numerical Simulationmentioning
confidence: 99%
“…The microscopic version of the Andronikashvili experiment was first conducted by Grebenev et al in 1998. [8] They measured the rovibrational spectrum of OCS doped in a 4 He droplet with thousands of atoms at T 5 0.37 K. In the spectrum, the group observed a well-resolved rotational structure with a rotational inertia greater than that of a free OCS molecule.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, spectroscopic probes of molecular impurities in helium droplets have shown that while 4 He clusters result in superfluid behavior with free-rotor-like molecular spectra, 3 He atoms behave as a normal fluid and the impurity spectra are of hindered-rotor type. 1 Since 4 He atoms are composite spinless bosons and 3 He atoms are fermionic particles with a nuclear spin equal to 1/2, one fundamental question has concerned the influence of the spin and the antisymmetry of the fermionic 3 He wave-functions in providing such different response to the molecular rotation. QuantumChemistry (QC)-like Nuclear-Orbital (NO) approaches, first introduced by Jungwirth and Krylov, 2 map the problem onto an electronic structure-like problem by considering the helium atoms as pseudo-electrons and the dopant molecule as a structured pseudo-nucleus, replacing Coulomb interactions by van der Waals He-He and He-dopant pair potentials.…”
Section: Introductionmentioning
confidence: 99%